5,6-Dihydro-[1,2,4]triazolo[1,5-с]quinazolines. Message 3. Synthesis of 2-aryl-5-trichloromethyl-5,6-dihydro[1,2,4]triazolo[1,5-с]quinazolines and their reactivity towards N-nucleophiles - Kholodnyak, S. V.; Voskoboynik, O. Yu.; Kovalenko, S. I.; Sergeieva, T. Yu.; Okovytyy, S. I.; Shishkina, S. V.; Холодняк, Сергій Валерійович; Воскобойнік, Олексій Юрійович; Коваленко, Сергій Іванович; Сергеєва, Тетяна Юріївна; Оковитий, Сергій Іванович; Шишкіна, С. В. (НФаУ, 2016)
Features of 5-trichloromethyl-2-aryl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines formation as result of [5+1]-cyclocondensation of the corresponding [2-(3-aryl-1H-1,2,4-triazole-5-yl)phenyl]amines with chloral hydrate are described in the article. It has been shown that this transformation is regioselective, occurs by refluxing of the initial compounds in acetic acid with formation of 2-aryl-5-trichloromethyl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines. The possible mechanism of 5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines has been proposed and substantiated. It has been shown that the reaction proceeds as step-by-step transformation that includes ANE and AN processes. The 2-phenyl-5-trichloromethyl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazoline obtained was studied in reactions with N-nucleophiles. It has been found that regardless of the nature of nucleophile the reaction mentioned above leads to formation of 2-phenyl-5-(dichloromethyl)-[1,2,4]triazolo[1,5-c]qinazoline. The mechanism of the transformation mentioned above is given; it is β-elimination on the Е1cb-mechanism followed by isomerisation. The structure of the compounds synthesized has been confirmed by the complex of physicochemical methods, including 1H-, 13C-NMR-spectrometry, chromato-mass spectrometry, mass-spectrometry and X-ray structural study. A detailed analysis of 1H and 13C-NMR spectral data of the compounds synthesized has been conducted. It has been found that the signals of the carbon atom in position 5 at 79.25-77.95 ppm were characteristic for 2-aryl-5-trichloromethyl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines, whereas aromatization of the molecule leads to signiŰcant deshielding of this carbon atom (163.41 ppm). The prospects of further chemical modiŰcation of 2-aryl-5-(dichloromethyl)-[1,2,4]triazolo[1,5-c]quinazolines has been discussed.
5,6-дигідро-[1,2,4]триазоло[1,5-с]хіназоліни. Повідомлення 3. Синтез 5-трихлорометил-2-арил-5,6-дигідро-[1,2,4]триазоло[1,5-с]хіназолінів і їх реакційна здатність по відношенню до N-нуклеофілів
Keywords: 2-aryl-5-trichloromethyl-5,6-dihydro[l,2,4]triazolo[l,5-c]quinazolines; [5+l]-cyclocondensation; N-nucleophiles; elimination